The Influence of the Regional House of Representatives’ Legislative Function Performance on the Protection of Indigenous Peoples’ Rights in Central Maluku Regency - Herry Men Carl Haurisa; Mohamad Arsad Rahawarin; Hendry Selanno (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to examine the influence of the DPRD’s legislative performance on the protection of indigenous peoples’ rights in Central Maluku Regency, focusing on how legislative actions contribute to safeguarding customary land, natural resources, and cultural identity. This study used a quantitative approach with a full sampling technique involving all 40 members of the Central Maluku Regency DPRD. Data were collected through a structured questionnaire and processed using simple linear regression with statistical software to measure the causal influence of legislative performance. The study found that DPRD legislative performance has a positive and significant effect on the protection of indigenous peoples’ rights. The regression coefficient of 0.643 and R² value of 0.819 indicate that legislative performance explains a substantial proportion of variations in rights protection, confirming the research hypothesis and demonstrating the DPRD’s strategic role. This study provides empirical evidence on the direct quantitative influence of legislative performance on indigenous rights protection at the regional level. It advances existing knowledge by offering measurable indicators of legislative effectiveness and highlighting the importance of strengthening institutional capacity to enhance substantive protection outcomes.